2020
DOI: 10.1534/g3.119.400985
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Split Homing Based Gene Drive for Efficient Knockout of Multiple Genes

Abstract: Homing based gene drives (HGD) possess the potential to spread linked cargo genes into natural populations and are poised to revolutionize population control of animals. Given that host encoded genes have been identified that are important for pathogen transmission, targeting these genes using guide RNAs as cargo genes linked to drives may provide a robust method to prevent disease transmission. However, effectiveness of the inclusion of additional guide RNAs that target separate genes has not been thoroughly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 70 publications
2
113
0
Order By: Relevance
“…Building suppression gene drives for mosquito control that are fit for purpose requires a combination of the following features: optimal target sites that show high functional constraint; the targeting of multiple sites by the same gene drive construct; fine tuning of the expression of the nuclease that serves as the gene drive's 'motor' in order that the drive shows the most efficient invasion dynamics. A number of these theorised improvements to design have been substantiated: multiplexing through the use of multiple guide RNAs in a single drive construct has been shown to improve robustness of the drive [12,20,35]; judicious choice of functionally constrained sites in essential genes has meant that gene drives targeting such sites do not generate resistant alleles that are selected, at least in the laboratory [8,35]. For the last aspect -optimising expression -we have shown here that simple changes to the promoter controlling nuclease activity can lead to drastic improvements in the speed of invasion due to two principle reasons: 1) less propensity to induce end-joining repair in the germline and 2) improved fecundity of 'carrier' females that contain a single copy of the gene drive and transmit it in a super-Mendelian fashion to their offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building suppression gene drives for mosquito control that are fit for purpose requires a combination of the following features: optimal target sites that show high functional constraint; the targeting of multiple sites by the same gene drive construct; fine tuning of the expression of the nuclease that serves as the gene drive's 'motor' in order that the drive shows the most efficient invasion dynamics. A number of these theorised improvements to design have been substantiated: multiplexing through the use of multiple guide RNAs in a single drive construct has been shown to improve robustness of the drive [12,20,35]; judicious choice of functionally constrained sites in essential genes has meant that gene drives targeting such sites do not generate resistant alleles that are selected, at least in the laboratory [8,35]. For the last aspect -optimising expression -we have shown here that simple changes to the promoter controlling nuclease activity can lead to drastic improvements in the speed of invasion due to two principle reasons: 1) less propensity to induce end-joining repair in the germline and 2) improved fecundity of 'carrier' females that contain a single copy of the gene drive and transmit it in a super-Mendelian fashion to their offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, deposited nos and zpg mRNA concentrate at the germ plasm due to regulatory signals present on the untranslated regions, which also further restrict translation of maternal mRNAs to the germline [14,19]. The promoter region of exuperantia has been validated in Drosophila [20] and in the tiger mosquito, Aedes aegypti, has been used to drive robust expression in both male and female germlines and has recently been used to control expression of Cas9 in a split gene drive system in this mosquito [21,22]. In contrast to zpg and exu, several reports have suggested that nos is specific to the female germline in mosquitoes, however promoter fusions in Aedes aegypti and Anopheles gambiae led to low level expression in males perhaps due to incomplete recapitulation of endogenous gene expression [23][24][25].…”
Section: Choice Of Germline Promotersmentioning
confidence: 99%
“…(Buchman et al, 2020(Buchman et al, , 2019Hoermann et al, 2020;Isaacs et al, 2012;Marshall et al, 2019)), or population suppression (Hammond et al, 2016;Kyrou et al, 2018;Simoni et al, 2020) to reduce and eliminate wild disease transmitting populations of mosquitoes. Despite significant progress, HGDs are still an emerging technology that can suffer from the formation of resistance alleles, hindering their efficacy (Adolfi et al, 2020;Carballar-Lejarazú et al, 2020;Gantz et al, 2015;Hammond et al, 2016;Kandul et al, 2019a;Kyrou et al, 2018;Li et al, 2020;Pham et al, 2019;Simoni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This enables the HGD to home, or copy, itself into the recipient allele (Champer et al, 2016;Esvelt et al, 2014) (referred to as homing from hereon). This general design for HGD was quickly adopted, and many HGDs were developed in several insect species (Gantz et al, 2015;Hammond et al, 2016;Kandul et al, 2019a;Kyrou et al, 2018;Li et al, 2020;Simoni et al, 2020). However, it soon became apparent that HGDs unintentionally promote the formation of resistance alleles through mutagenic repair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation